Revisiting innovative approaches to teaching and learning in nursing programmes: Educators’ experiences with the use of a case-based teaching approach at a nursing school - Adejumo, O (South African Journal of Higher Education, 2016)
Innovative approaches to teaching and learning have been acclaimed by educators in health care related professions as more suitable to teaching the future professionals, to engender critical thinking, as well as competencies that are relevant to the needs of the society. This paper focuses on teachers concerns about the implementation of the case-based method of teaching at a nursing school. Teachers involved in this method of teaching for at least 2 years provided qualitative data through a series of focus group discussions (4 FGDs) organised according to the different year levels of the nursing programme of the school, so as to be able to contextualise answers to the study questions. The FGDs were followed by a 1-day consensus workshop for finding solutions for the future. Concerns raised included issues about the facilitation role of the teacher, the role of the student, curriculum alignment, assessment methods, and the role of the environment in case-based teaching and learning settings. Recommended solutions were aligned to the identified concerns.